Efeito da adição de diferentes nutrientes na dieta sobre a qualidade das carcaças e prevenção de peito madeira e estrias brancas em frangos de corte - Vargas, Lérida Fantin de (2019)
Technological advances in genetic selection and in the processing of poultry allow the production of chickens with greater live weight in less time. This increase in muscle cell size and growth rate has led in the last decade to the appearance of several myopathies that cause lesions in the muscle fibers and connective tissues, mainly in the breast (Pectoralis major). Myopathies are changes in muscle tissue normality, of which the white striping (WS) is characterized by the presence of white intramuscular lines, and the wooden breast (WB) is characterized by the formation of fibers with firm texture and resistant to compression covered with clear fluid and viscous, both myopathies cause sensory rejection and impair the functionality of the meat. The objective of this work was to evaluate the effect of the supplementation of manganese (Mn), copper (Cu), purified nucleotides and guanidinoacetic acid (GAA) in the poultry diet on carcass quality and prevention of myopathies in the breast. A total of 1500 mixed-cutting chicks were used and the supplementation of GAA (600 ppm), purified nucleotides (1000 ppm) and minerals and Manganese (40 ppm) and Copper (7 ppm), grouped into twelve treatments. The poultry were kept in an experimental aviary with structure and standardized management parameters up to 42 days of age and slaughtered in a poultry slaughterhouse. The combined use of Cu, Mn, and GAA (T12), applied to the broilers basic feed, promoted a significant reduction in relation to control (T1) in the incidence of soft WS (25.48 vs 33.46%), moderate WS (14.21 vs 17.46%), severe WS (9.98 vs 20.13%), soft WB (7.17 vs 14.79%) and severe WB (2.94 vs 6.79%), respectively. As was the treatment that presented the highest occurrence of normal breast in relation to the control, that is, without WB (80.41 vs 70.79%) and WS (50.83 vs 29.46%). The supplementation used in all treatments did not change the physical-chemical parameters (water retention capacity, cook loss, pH15min, pH24h, moisture, protein and fat), yield (carcass, legs, wings, inner fillet, boned chest and back) and performance (live weight, feed intake, weight gain and feed conversion), relative to the control. When assessing simultaneously the occurrence of dermatosis and cellulitis, treatment supplemented with GAA (T3) seems to present a lower occurrence in relation to the control. The post-mortem lesions observed during the macroscopic examination of WS and WB corresponded to the degree of classification used (normal, soft, moderate and severe) and could be applied satisfactorily during the industrial process of the chicken.